THE ANALYSIS OF NON-REFOULEMENT PRINCIPLE TOWARDS ROHINGYA REFUGEES IN BANGLADESH - Gunawan, Yordan; Rettob, Abdullah Teguh Thamrin; Kalagita, Kevin (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2020)
Crime against humanity is still happening in some parts of the world for several reasons, includes the conflict of interest, politics as well as religion. It makes the victims like the Rohingya ethnic have to flee for finding peace and a secure place to survive. Non-Refoulement Principle which stated in 1951 Refugee Convention is being an important principle as the tools to protect the refugee and stateless person. In the Rohingya case, Bangladesh has argued about the ‘security problem’ of Rohingya’s pose, and Bangladesh also stated it became an important reason in sending the Rohingya back. From March 1, 2019, Bangladesh Authority no longer accepts refugees from Rohingya. The research aims to know further on the implementation of Non-Refoulement principle. In addition, the research was made by using library research analysis as the method of research; whole data and information that contained on the research were collected through literature review by referring to books, journals, articles and websites. The research found that Bangladesh does not apply the Non-Refoulement principle and violates the Humanitarian Assistance principle. Even though ‘security issues’ have been raised as land to repatriate refugees by Bangladesh to Myanmar, it cannot be applied and impose Non-Refoulement obligations to Bangladesh as a matter of customary international law.